Hospital-reported Pneumococcal Susceptibility to Penicillin - Metlay, Joshua P. (Centers for Disease Control and Prevention, 2004)

(untitled)
Geographic variation in drug susceptibility among isolates of Streptococcus pneumoniae has influenced national treatment guidelines for community-acquired pneumonia. Whether individual hospital susceptibility data provide reliable and valid information for providers is unclear. We examined the geographic and temporal variability in hospital-reported rates of pneumococcal susceptibility. We surveyed all 52 hospitals that provided acute adult care in the five counties surrounding Philadelphia and collected data on levels of penicillin susceptibility among all pneumococcal blood isolates from 1998 to 2000. In 1998, pneumococcal nonsusceptibility to penicillin varied from 0% to 67% of all blood isolates across the 33 hospitals with >10 isolates in that year. Hospital location did not correlate with the level of reported pneumococcal susceptibility (p = 0.8). In addition, correlations were not significant in reported pneumococcal susceptibility to penicillin within individual hospitals during the 3 years.